2021
DOI: 10.3390/ijerph18084330
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cigarillo Packaging Characteristics on Young Adult Perceptions and Intentions: An Experimental Study

Abstract: Research demonstrates that characteristics of cigarette packaging influence consumer product perceptions, yet the current literature on the impact of cigar packaging is limited. This study aims to examine how different cigarillo packaging features influence young adult cigar smokers’ perceptions. In 2016, we recruited past-year cigar users aged 18–34 from Amazon Mechanical Turk (N = 1260). We utilized a 2 × 2 × 3 × 2 between-subjects factorial design, randomly assigning participants to view one of 24 images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Our finding that most ad occurrences featured the brand’s cigar pack is noteworthy given the importance of brand recognition for purchasing at the point-of-sale, and the emerging literature on the impact of cigar packaging on consumer perceptions and intentions [ 42 , 43 , 44 , 45 , 46 ]. For example, one experimental study of cigarillo smokers found that elements of Black & Mild packaging, including the logo and brand name, presence of a price promotion, and pack color, influenced positive perceptions of the brand, such as smelling nice, containing high quality tobacco, reduced harshness, as well as intentions to purchase the product [ 42 ]. Therefore, the nearly ubiquitous presence of Black & Mild packaging in their magazine ads may reinforce and augment positive associations with the brand, above and beyond the content and language in the ad itself.…”
Section: Discussionmentioning
confidence: 78%
“…Our finding that most ad occurrences featured the brand’s cigar pack is noteworthy given the importance of brand recognition for purchasing at the point-of-sale, and the emerging literature on the impact of cigar packaging on consumer perceptions and intentions [ 42 , 43 , 44 , 45 , 46 ]. For example, one experimental study of cigarillo smokers found that elements of Black & Mild packaging, including the logo and brand name, presence of a price promotion, and pack color, influenced positive perceptions of the brand, such as smelling nice, containing high quality tobacco, reduced harshness, as well as intentions to purchase the product [ 42 ]. Therefore, the nearly ubiquitous presence of Black & Mild packaging in their magazine ads may reinforce and augment positive associations with the brand, above and beyond the content and language in the ad itself.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, findings not only revealed no differences in the importance of the graphic design of the cigarillo pack but also low ratings overall and across all sub-populations. Given that prior experimental studies show evidence for the impact of cigarillo package color and design on young adults' perceptions [14][15][16], we speculate that this discrepancy between prior experimental findings and self-reported survey data from this study may be due to people's unwillingness to admit their susceptibility to marketing (and their belief that while everyone else may be influenced, they are not-a phenomenon known as the third-person effect) [28]. Thus, participants may be rating package design as low in importance, while compensating for…”
Section: Discussionmentioning
confidence: 99%
“…These data were derived from an experiment designed to assess product preferences, perceptions and behaviors among young adults and were collected using Amazon Mechanical Turk (MTurk) in 2016 [15]. Eligibility criteria included a) being 18-34 years old and b) having used a cigar (i.e., any type of cigar or cigarillo or smoked a blunt) in the past 12 months.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since cigarillo use is less frequent than cigarette smoking,9 we assessed cigarillo use with two items 37 38. The first item focused on past year use and asked, ‘How many times in the past 12 months have you smoked a cigarillo?’, with answer options for 1 time, 2–5 times, 6–10 times, 11–20 times, 21–30 times, 31–50 times and more than 50 times.…”
Section: Methodsmentioning
confidence: 99%